Daya Terima Kandungan Protein dan Zat Besi pada Sosis Ikan Kembung dan Hati Ayam - Nahda Fadhilah Fadhilah; Sunarto; Fatmawaty Suaib (Nutrition Science and Health Research, 2025)
Stunting and anemia are two major nutritional problems that are closely related and affect the growth and development of children. According to SSGI 2022, the prevalence of stunting in Indonesia was 21,6%, while anemia among toddlers reached 38,5% (Riskesdas, 2018). Prevention efforts can be carried out by consuming foods high in protein and heme iron, such as mackerel and chicken liver. This study aimed to determine the acceptability, protein content, and iron (Fe) levels in sausage made from mackerel and chicken liver as an alternative food to prevent stunting and anemia in toddlers. The research used a completely randomized design (CRD) with three sausage formulations: F1 (80% mackerel:20% chicken liver), F2 (70%:30%), and F3 (60%:40%). Acceptability was tested organoleptically by 30 panelists on four attributes: color, aroma, texture, and taste. Protein content was analyzed using the Kjeldahl method, and iron was measured using spectrophotometry. Data were analyzed using the Kruskal Wallis test and continued with the Mann Whitney test. The results showed that Formula F1 had the highest overall preference. Significant differences were found in aroma (p = 0,015) and texture (p = 0,024). Nutritional analysis of F1 showed a protein content of 42% and iron of 1,5 mg/100 g. Mackerel and chicken liver sausage, particularly formula F1, had good acceptability and high nutritional content, making it a potential alternative food to help prevent stunting and anemia in toddlers.